Exploring rare coding variants in UK biobank: preliminary associations with motor neuron disease - Hu, Zhen; Wan, Jing-jin; Yan, Qin-qin; Fan, Yu; Liu, Jun (Frontiers in Aging Neuroscience, 2026)
IntroductionPrevious studies have illuminated a significant genetic component in motor neuron disease (MND) pathogenesis, with several causative genes identified. However, a substantial proportion of MND cases remain genetically unexplained, particularly regarding the comprehensive contribution of rare, high-impact variants across the exome.MethodsLeveraging whole-exome sequencing data from nearly half a million UK Biobank participants, we systematically investigated the association between high-confidence protein-truncating variants (HC PTVs) and MND risk in a Caucasian subset. Our large-scale gene-based association analysis utilized REGENIE software and LOFTEE-defined HC PTVs.ResultsWe identified significant preliminary associations between HC PTVs in 14 genes and an increased risk of MND. Notably, while NEK1 has been previously implicated in ALS, the remaining 13 genes (BLVRB, KLHL32, RIMS2, DYDC2, DCBLD1, ANXA4, COMP, TRIM42, ANO4, NFX1, CFAP206, CKAP2L, and ANGPTL4) show preliminary associations as novel candidate loci for the disease. Functional enrichment analyses further indicated that these genes are significantly involved in critical biological pathways, including collagen-containing extracellular matrix organization and ciliary function. Furthermore, tissue specificity analysis highlighted a strong enrichment of these genes’ expression in brain regions, with the hypothalamus showing the highest specificity.DiscussionThese findings suggest a potential expansion of the known genetic landscape of MND, and highlight novel biological pathways implicated in its pathogenesis. This study underscores the power of large-scale population genetics in uncovering critical disease mechanisms and offers new avenues for mechanistic research and therapeutic development for MND, pending independent validation.